Effect of tumor properties on energy absorption, temperature mapping, and thermal dose in 13.56-MHz radiofrequency hyperthermia. (May 2018) - Prasad, Bibin; Kim, Subin; Cho, Woong; Kim, Suzy; Kim, Jung Kyung
Abstract: Computational techniques can enhance personalized hyperthermia-treatment planning by calculating tissue energy absorption and temperature distribution. This study determined the effect of tumor properties on energy absorption, temperature mapping, and thermal dose distribution in mild radiofrequency hyperthermia using a mouse xenograft model. We used a capacitive-heating radiofrequency hyperthermia system with an operating frequency of 13.56 MHz for in vivo mouse experiments and performed simulations on a computed tomography mouse model. Additionally, we measured the dielectric properties of the tumors and considered temperature dependence for thermal properties, metabolic heat generation, and perfusion. Our results showed that dielectric property variations were more dominant than thermal properties and other parameters, and that the measured dielectric properties provided improved temperature-mapping results relative to the property values taken from previous study. Furthermore, consideration of temperature dependency in the bio heat-transfer model allowed elucidation of precise thermal-dose calculations. These results suggested that this method might contribute to effective thermoradiotherapy planning in clinics. Highlights: Effect of tumor property is investigated in radiofrequency hyperthermia. Dielectric property variations in tumor should be considered carefully in hyperthermia-treatment planning. Dielectric property variation and temperature dependency could improve the accuracy of thermal dose calculations. Our study contributes to effective thermoradiotherapy planning in clinics.